PENGARUH KOMPOSISI PENJUALAN EKSPOR, COST OF GOODS SOLD RATIO DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON ASSET PADA PT BUKIT ASAM TBK PERIODE 2015-2024 - Fachreza Via Cahya; Mardiana, Sri (Journal Economics Technology And Entrepreneur, 2025)
: This study aims to investigate the impact of Export Sales Composition, Cost of Goods Sold Ratio, and Total Asset Turnover on PT Bukit Asam Tbk's Return on Assets from 2015 to 2024. This study employs an associative descriptive method with a quantitative approach. Ten years' worth of PT Bukit Asam Tbk financial statements make up the sample. Multiple linear regression, hypothesis testing, determination coefficient analysis, and traditional assumption testing are examples of data analysis. Y = 29.006 – 0.060 (X1) – 0.580 (X2) + 0.334 (X3) + e is the regression model that was generated. Export Sales Composition partially has no significant impact on ROA, as indicated by tcount < ttable (–0.189 < 2.447) and a significance threshold of 0.856 > 0.050. With tcount > ttable (5.152 > 2.447) and significance 0.002 < 0.050, the Cost of Goods Sold Ratio significantly and favorably affects ROA. With tcount > ttable (3.887 > 2.447) and significance 0.008 < 0.050, total asset turnover likewise exhibits a positive, significant impact on ROA. Fcount > Ftable (16.582 > 4.760) and significance 0.003 < 0.050 show that all three factors simultaneously have a significant impact on ROA. 89.2% was the coefficient of determination. Other characteristics and conditions that were not investigated had an impact on the remaining 10.8%.